Kombinasi Brain Gym Dan Memory Games Terhadap Peningkatan Fungsi Kognitif Pada Lansia - Moh Hanafi; Pramono Giri Kriswoyo; Novema Ashar Nurahman (Jurnal Kesehatan, 2025)
Cognitive decline in older adults is a serious problem that affects independence and quality of life and increases the risk of dementia. Brain gym therapy and matching card games have been shown to stimulate cognitive function; however, the combination of these two interventions has not been widely studied scientifically. As the elderly population continues to grow, effective, evidence-based prevention and management strategies are urgently needed. The aim of this study was to determine the effectiveness of a combination of brain gym and matching card game interventions in improving cognitive function among older adults. This study employed a quantitative approach with a pre-experimental one-group pretest post-test design. A total of 35 respondents were selected using purposive sampling with restrictive criteria. Cognitive function was measured using the Mini-Mental State Examination (MMSE). Data were analysed using the Wilcoxon test. The results showed that among the 35 elderly participants, 77% were aged 60–74 years, 83% were female, and 54% had an elementary school education. There was a significant difference in cognitive scores before and after the implementation of the combined brain gym and matching card game intervention, with a p-value of 0.00. It can be concluded that the combination of brain gym and the matching card game has a significant effect on improving cognitive function in older adults